2003
DOI: 10.1021/jp035443e
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Hydration of U(IV), U(V), and U(VI) Dioxo Monocations

Abstract: The formation of adduct ions consisting of uranium oxycations and water was studied using an ion trap-secondary ion mass spectrometer. The U(IV) and U(V) species [UO(OH)]+ and [UO2]+ were produced by bombarding the surface of UO3 using molecular primary ions, and the U(VI) species [UO2(OH)]+ was generated by O2 oxidation of [UO(OH)]+ in the gas phase. All three ions formed H2O adducts by termolecular association reactions:  [UO(OH)]+ (a U(IV) species) added three water molecules, for a total of five ligands; [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
77
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 59 publications
8
77
1
Order By: Relevance
“…Because only the ion at m/z 270 was isolated for storage in the ion trap, the m/z 288 peak observed in Figure 4 is an H 2 O adduct to m/z 270 formed by an association reaction in the gas phase. However, the intensity of m/z 288 (Ͻ5% relative to m/z 270) is vastly lower than the peak at the same m/z that was an apparent product ion generated by the CID of investigation that demonstrated slow hydration rates for the reduced uranyl ion produced by ion induced sputtering of solid UO 3 [42]. We propose instead that the product may be generated via the reaction:…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Because only the ion at m/z 270 was isolated for storage in the ion trap, the m/z 288 peak observed in Figure 4 is an H 2 O adduct to m/z 270 formed by an association reaction in the gas phase. However, the intensity of m/z 288 (Ͻ5% relative to m/z 270) is vastly lower than the peak at the same m/z that was an apparent product ion generated by the CID of investigation that demonstrated slow hydration rates for the reduced uranyl ion produced by ion induced sputtering of solid UO 3 [42]. We propose instead that the product may be generated via the reaction:…”
Section: Resultsmentioning
confidence: 78%
“…The formation of abundant H 2 O adducts indicates that several of the uranyl complex ions show a significant tendency to accept ligands via gas-phase association reactions in the ion trap. The reaction kinetics for the addition of one or more H 2 O ligands to UO 2 ϩ and related species generated by ioninduced sputtering of solid UO 3 was recently investigated [42]. While beyond the scope of the present study, the reaction kinetics for the addition of H 2 O ligands to the various CID products generated from the alcohol coordinated complexes containing UO 2 2ϩ were also investigated and will be the subject of a separate report [43].…”
Section: Resultsmentioning
confidence: 99%
“…In both experiments, the ion-molecule reaction times were the same as for m/z 301 (180 s) but the pressures were slightly different (2.4 ϫ 10 Ϫ8 torr for D 2 O and 4.8 ϫ 10 Ϫ8 torr for CD 3 OD). UO 2 ϩ reacts readily with CD 3 OD by adding three and four CD 3 4 ] ϩ in ion trap studies at higher partial pressures of water [17].…”
Section: Ion-molecule Reactions In the Gas-phase With D 2 O And Cd 3 mentioning
confidence: 99%
“…Many of these studies have focused on the reactions of U ϩ and UO ϩ with alkanes [6,7], alkenes [8], alcohols, thiols and ethers [9], arenes [10], and other small molecules [11][12][13][14][15][16]. Recently, the hydration reactivities of UO ϩ , UO 2 ϩ , and UO 2 2ϩ were examined using secondary ion mass spectrometry [17]. These studies used surface ionization [11,12], pulsed glow discharge [13,14], or laser ablation [6 -11, 13, 16, 17] techniques to create uranium ions for study.…”
mentioning
confidence: 99%
“…O 2 reactions with ionic Cr oxide species were conducted by Bricker and Russell [32], who concluded that O 2 would bind with Cr carbonyl anions in a molecular fashion, but gas-phase studies of Cr oxyanions more typical of the condensed phase have not been conducted. Here, O 2 oxidation of Cr 1,2 O y H z Ϫ species is examined using an ion trap SIMS instrument; this approach has been effective for elucidating reaction pathways and kinetics for ionic Al [33,34], Si [34], and U oxides [35]. The results show that under the ambient conditions of the ion trap (1 ϫ 10 Ϫ4 torr He, 310 K), Cr 1,2 O y H z Ϫ species containing low-coordinate, low oxidation state metal centers underwent oxidation.…”
mentioning
confidence: 99%